Exact relativistic maxwellian magnetized plasma dielectric tensor evaluation for arbitrary wave numbers - Pavlov, S.S. (Вопросы атомной науки и техники, 2016)
A new exact integral form of the fully relativistic permittivity tensor for plasmas in a magnetic field is given. It is
suitable for numerical applications for arbitrary wave numbers since all integrals in it are one-dimensional ones.
This form is interesting for applications to study propagation and absorption of electron Bernstein waves in the
laboratory thermonuclear plasmas and of arbitrary electron and ion cyclotron waves in the hot astrophysical
plasmas. Даётся новая интегральная форма полностью релятивистского тензора диэлектрической проницаемости
плазмы в магнитном поле. Она годится для численных приложений при произвольных волновых числах,
поскольку все интегралы в ней являются одномерными. Эта форма представляет интерес с точки зрения
приложений для изучения бернштейновских электронных циклотронных волн в лабораторной термоядерной
плазме и произвольных электронных и ионных циклотронных волн в горячей астрофизической плазме. Дається нова інтегральна форма повністю релятивістського тензора діелектричної проникності плазми в
магнітному полі. Вона годиться для численних додатків при довільних хвильових числах, оскільки всі
інтеграли в ній є одновимірними. Ця форма являє інтерес з точки зору додатків для вивчення
бернштейнівських електронних циклотронних хвиль в лабораторній термоядерної плазмі і довільних
електронних та іонних циклотронних хвиль в гарячій астрофізичної плазмі.